“Ministry of Presence” as Emotional Labor: Perspectives from Recipients of Care - Lawton, Amy (Religions, 2024)
This paper analyzes the work of chaplaincy and spiritual care from the perspective of care recipients. Chaplains call their work a “ministry of presence,” a term of art that is often unclear to many who are not chaplains. How else might we conceptualize “presence” in order to ground it in the social science literature? Using sociological theory, we show that care recipients may experience a chaplain’s work as emotional labor, specifically “other-focused emotional labor.” Based on in-depth interviews with a sample of 38 care recipients, we find recipients feeling reassured by the chaplain; being offered support and help by the chaplain; and not feeling judged by the chaplain. These findings enlarge sociological concepts about spiritual care to include what recipients experience as emotional labor and call for a broader engagement between sociologists of religion and emotions.